2001
DOI: 10.1108/09544780110360615
|View full text |Cite
|
Sign up to set email alerts
|

Quality training: findings from a European survey

Abstract: Quality management is an essential part of an organisation's competitive strategy. The training that underpins quality management determines the likely effectiveness of the quality initiatives undertaken. This article details the findings of a questionnaire survey into the training provided to support quality management. A total of 450 responses are analysed. Findings from the UK, Portugal and Finland are compared to identify differences in national practice. Training provision is definitely focused at quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Training employees facilitates the updating of skills, leads to increased employee satisfaction (Acton & Golden, 2003), increased employee commitment to the organization (Bushardt, Fretwell, & Cumbest, 1994), and strengthens the organization's competitiveness (Hughey & Mussnug, 1997;Burden & Proctor, 2000). Although company commitment to training may lead to those potential benefits, there are many different categories and types of training (Switzer & Kleiner, 1996;Huang, 2001;Mathews, Ueno, Periera, Silva, Kekal, & Repka, 2001) and training delivery mechanisms (Acton & Golden, 2003). With regard to IT training, Benamati and Lederer (2001) found that education and training was the most frequently applied coping mechanism to handle changing IT, though managers might question whether they use it sufficiently.…”
Section: It Trainingmentioning
confidence: 99%
“…Training employees facilitates the updating of skills, leads to increased employee satisfaction (Acton & Golden, 2003), increased employee commitment to the organization (Bushardt, Fretwell, & Cumbest, 1994), and strengthens the organization's competitiveness (Hughey & Mussnug, 1997;Burden & Proctor, 2000). Although company commitment to training may lead to those potential benefits, there are many different categories and types of training (Switzer & Kleiner, 1996;Huang, 2001;Mathews, Ueno, Periera, Silva, Kekal, & Repka, 2001) and training delivery mechanisms (Acton & Golden, 2003). With regard to IT training, Benamati and Lederer (2001) found that education and training was the most frequently applied coping mechanism to handle changing IT, though managers might question whether they use it sufficiently.…”
Section: It Trainingmentioning
confidence: 99%
“…Many forms of training exist (Wiedenbeck, Zila et al, 1995;Switzer and Kleiner, 1996;Huang, 2001;Mathews, Ueno et al, 2001). The range of training techniques has been expanded by the application of technology in its "hard" (for example through computing technology) and "soft" (for example through instructional design) (Sadler-Smith, Down et al, 2000).…”
Section: Types Of Trainingmentioning
confidence: 99%
“…They found that the top ten training methods used in business, listed in order from highest to lowest use, were: videotapes, lectures, one-on-one instruction, role plays, games/simulation, case studies, slides, computer-based training, audio tapes, and films. In a survey carried out by 450 respondents, Mathews et al (2001) studied the incidence of training delivery methods across non-industry specific organizations in the U.K., Portugal, and Finland within the context of benefits accrued. They found that training methods most commonly used tended to be traditional, with little impact evident of more hitech methods.…”
Section: Types Of Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In hindsight, some implementation mistakes were made, and some aspects of the system did not work as well as they should have. A lack of suitable staff training was one reason for these problems (Matthews, Ueno, Periera, Silva, Kekal and Repka 2001).…”
Section: Introductionmentioning
confidence: 99%